The ECB Monetary Strategy: A Critical Assessment - Rodríguez Fuentes , Carlos J.; Padrón Marrero , David (Revista de Economía Crítica, 2021)
This paper aims to provide a critical assessment of the performance of the ECB’s monetary strategy, as well as of the substantial "de facto" changes this strategy has undergone from 2010 onwards. These changes have occurred as a consequence of the unforeseen challenges that the eurozone crisis posed to its implicit conventional monetary model of "two pillars". The standpoint of the paper is that the institutional changes the eurozone requires cannot be limited to the so-called institutional failures in the architecture of the European monetary union, but should also be extended to reconsider the underlying theoretical framework that inspires the ECB’s monetary strategy.